Environmentally friendly, photochemical access to [N^C^N] AuIII pincer complexes by oxidative addition - Eppel, Daniel; Penert, Philipp; Stemmer, Johanna; Bauer, Christina; Rudolph, Matthias; Brückner, Margit; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2021)
Starting from commercially available DMSAuCl and diazonium salts, cationic [ ]AuIII complexes were synthesized in a selective, photosensitizer-free, photochemical reaction by irradiation with blue LED light. This new protocol represents the first easy synthesis of these types of pincer complexes in moderate to excellent yield starting from a readily available gold(I) precursor with nitrogen as the only by-product. Owing to the disadvantages of known protocols, especially the toxicity in the case of a transmetalation with mercury or the necessity for a mostly twofold excess of a gold precursor, this method offers an attractive alternative towards this kind of gold(III) complexes. In addition, the first arylated [ ]Au(III) pincer complex was synthesized by using this technology.